New Zealand Theosophists in "New Education" networks, 1880s-1938. Issue 1 (5th June 2017) - Middleton, Sue C.
Abstract : Purpose: It is well-known that Beatrice Ensor, who founded the New Education Fellowship (NEF) in 1921, was a Theosophist and that from 1915 the Theosophical Fraternity in Education she established laid the foundations for the NEF. However, little research has been performed on the Fraternity itself. The travels of Theosophists, texts, money and ideas between Auckland, India and London from the late nineteenth century offer insights into "New Education" networking in the British Commonwealth more broadly. The paper aims to discuss these issues. Design/methodology/approach: This paper draws on archival documents from the Adyar Library and Research Centre, International Theosophical Society (TS) headquarters, Chennai, India; the archive at the headquarters of the New Zealand Section of the TS, Epsom, Auckland; the NEF files at the archive of the London Institute of Education; papers past digital newspaper archive. Findings: New Zealand's first affiliated NEF group was set up by the principal of the Vasanta Gardens Theosophical School, Epsom, in 1933. She was also involved in the New Zealand Section of the Theosophical Fraternity, which held conferences from 1917 to 1927. New Zealand's Fraternity and Theosophical Education Trust had close links with their counterparts in England and India. The setting up of New Zealand's first NEF group was enabled by networks created between Theosophists in New Zealand, India and England from the late nineteenth century. Originality/value: The contribution of Theosophists to the new education movement has received little attention internationally. Theosophical educational theory and Theosophists' contributions to New Zealand Education have not previously been studied. Combining transnational historiography with critical geography, this case study of networks between New Zealand, Adyar (India) and London lays groundwork for a wider "spatial history" of Theosophy and new education.